Evolving role of seneca valley virus and its biomarker TEM8/ANTXR1 in cancer therapeutics - Corbett, Virginia; Hallenbeck, Paul; Rychahou, Piotr; Chauhan, Aman (Frontiers in Molecular Biosciences, 2022)
Oncolytic viruses have made a significant inroad in cancer drug development. Numerous clinical trials are currently investigating oncolytic viruses both as single agents or in combination with various immunomodulators. Oncolytic viruses (OV) are an integral pillar of immuno-oncology and hold potential for not only delivering durable anti-tumor responses but also converting “cold” tumors to “hot” tumors. In this review we will discuss one such promising oncolytic virus called Seneca Valley Virus (SVV-001) and its therapeutic implications. SVV development has seen seismic evolution over the past decade and now boasts of being the only OV with a practically applicable biomarker for viral tropism. We discuss relevant preclinical and clinical data involving SVV and how bio-selecting for TEM8/ANTXR1, a negative tumor prognosticator can lead to first of its kind biomarker driven oncolytic viral cancer therapy.